Innovation marketing literacy on analysis of corn farming in Madura / Muh. Syarif ... [et al.] - Syarif, Muh; Wildan, Muhammad Alkirom; Mohamed Jais, Ismie Roha; Retno Sari, Andria; Malwidi, Farhan; Jana, Miftahul (Universiti Teknologi Mara Selangor, 2023)
Innovation in marketing management in the corn farming industry is the most important issue in making marketing analysis of corn farms. Therefore, this research will describe and then analyze the comparison of marketing innovations that include Marketing, Strategy, and marketing between districts in Madura. Thus this research is expected to make marketing decisions in a timely manner to prevent marketing difficulties, it is also useful for business analysis among agricultural areas in existing districts as research sample data. In addition to marketing innovation, the analysis of this study also uses the size of the business and the type of farming business. This research is based on descriptive and quantitative research methods. Descriptive methods are used to explain the character of Marketing, Strategy, and marketing. Meanwhile, quantitative methods test the comparison of innovation analysis in different districts. The results will give an idea of the state of marketing and comparison of business areas. Thus, conclusions can be drawn that are useful for developing or improving the marketing management system.